2020
DOI: 10.1021/acs.jpcb.0c04253
|View full text |Cite
|
Sign up to set email alerts
|

On Calculating the Bending Modulus of Lipid Bilayer Membranes from Buckling Simulations

Abstract: The bending modulus is an important physical constant characterizing lipid membranes. Different methods have been devised for calculating the bending modulus from simulations, and one of them, named the buckling method, is nowadays widely used due to its simplicity and numerical stability. However, questions remain on the reproducibility, finite size effects, and interpretation of results on lipid mixtures. Here we explore the dependence of simulation results on the system size and the strain. We find that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 45 publications
6
40
0
Order By: Relevance
“…Here, the domain morphology likely plays a minor effect. Interestingly, a similar observation emerged from a recent coarse-grained simulation study on the elastic properties of lipid bilayers (Eid et al, 2020); it was shown indeed that, in the presence of phase separation, bilayer elastic properties (including both the bending modulus and the area compressibility modulus) are close to the values calculated for the softer component. The present investigation extends the previous conclusion to monolayers not showing proper phase separation, but still presenting structural heterogeneity in the form of dynamic nano-sized domains.…”
Section: Discussionsupporting
confidence: 76%
“…Here, the domain morphology likely plays a minor effect. Interestingly, a similar observation emerged from a recent coarse-grained simulation study on the elastic properties of lipid bilayers (Eid et al, 2020); it was shown indeed that, in the presence of phase separation, bilayer elastic properties (including both the bending modulus and the area compressibility modulus) are close to the values calculated for the softer component. The present investigation extends the previous conclusion to monolayers not showing proper phase separation, but still presenting structural heterogeneity in the form of dynamic nano-sized domains.…”
Section: Discussionsupporting
confidence: 76%
“…As long as the condensed domains are "cushioned" by the surrounding L E phase, the macroscopic properties of the monolayer such as compressibility resemble those of the L E phase. Interestingly, a similar observation emerged from a recent coarse-grained simulation study on the elastic properties of lipid bilayers; 67 (Fig. 3C).…”
Section: Discussionsupporting
confidence: 82%
“…From a molecular perspective, the formation of a stable NP–membrane complex is triggered by local and rare alterations of the membrane compactness, such as in-plane, out-of-plane, and orientational 66 lipid fluctuations opening the way to ligand translocation. Cholesterol hinders these lipid dynamics, 56 thus reducing NP uptake. These results suggest that the passive incorporation of NPs could be tuned, in vitro , by modulating any of the controlling factors of membrane fluidity, such as temperature, lipid composition, leaflet composition asymmetry, and membrane protein concentration and type.…”
mentioning
confidence: 99%